Morphologic and phylogenetic investigations revealed size-divergent clades in chelae morphotypes of freshwater prawn Macrobrachium vollenhovenii Herklots (Decapoda: Palaemonidae) in a lake and river system of Southwest Nigeria (2024)
Background The freshwater prawn Macrobrachium vollenhovenii is one of the largest Macrobrachium species, a biological agent against human schistosomiasis, and a cheap protein source in riverine communities in West Africa. However, its aquaculture development for sustainable utilization is challenged by cryptic identity amidst the pres- ence of morphotypes of unknown size and genetic relatedness. This study aimed to investigate the maximum sizes and evolutionary links of chelae morphotypes in M. vollenhovenii for precise identification and utilization in a 3x2 randomized block experimental design. Ninety biggest encountered samples of M. vollenhovenii chelae morpho- types-those possessing equal left and right side chelae, longer left chelae, and shorter left chelae—were obtained from fisherfolks' catches at each of Asejire Lake and Ogun River during peak seasons (July-September) bimonthly field survey, representing EAAL, LLAL, SLAL-GAALS, and EAOR, LLOR, SLOR-GAORS. These were analyzed for differences (p<0.05) in size-linked parameters-length (L (cm)), weight (W (g)), and condition factor (K). Specimens' 16S rRNA nucleotide sequences were utilized to infer phylogenetic linkages, single-nucleotide polymorphism (SNP), and amino acid translations alongside NCBI references (NCBIrefseq). Results Weight (W) and condition factor (K), among GAALs, for SLAL and LLAL were similar; EAAL was signifi- cantly lowest; among GAORS, SLOR and LLOR were similar; and EAOR was significantly lowest. In GAALS, EAAL, LLAL, and SLAL had higher L, W, and K than counterpart GAORS. Sequences formed two polyphyletic groups: EAOR branch from EAAL, in which 100.0%EA rooted 75.0% NCBIrefseqs, forming a clade; and GAOR-SLOR and LLOR branch form GAOR-LLAL rooted SLAL, in which 100.0%LL and SL rooted KJ463387.1 (Badagry), forming another clade. SNP Locus 91 separated 100.0%GAOR from 100.0%GAAL and 100.0%NCBIrefseqs translating to valine; SNP Locus 171 separated 100.0%EA and its co-rooted NCBIrefseqs from 100.0%LL, SL, and their co-rooted NCBIrefseq, translating to glycine/ glutamic acid change. Conclusion The equal left and right side chelae and the unequal left and right side chelae specimens are, respec- tively, small- and robust-sized, irrespective of habitat. They are divergent size-linked clades having protein translate differences, delineable at 16S rRNA SNP Locus 171; their size variant habitat strains are delineable at SNP Locus 91. These SNP markers will be useful for precision identification and selection of the size variant chelae morph strains for sustainable utilization.